Air return ratio measurements at the solar tower Jülich using a tracer gas method. (April 2017) - Tiddens, Arne; Röger, Marc; Stadler, Hannes; Hoffschmidt, Bernhard
Highlights: The first air return ratio measurement on a large scale receiver (10 kg air/s). An accuracy of ± 2% (95% coverage factor) has been reached. Environmentally friendly and thermally stable helium is used as tracer gas. Only one measurement point within the air circuit of the solar tower is required. Abstract: The air return ratio is a key factor for the overall efficiency of the open volumetric receiver concept. Although first measurements of the air return ratio exist for smaller setups of the open volumetric receiver concept, so far no measurement of the air return ratio has been presented for the Solar Thermal Test and Demonstration Power Plant Jülich ( ≈ 1.5 MW, ≈10 (kg air)/s; ≈700 °C). This paper describes the application of a tracer gas method at the solar tower Jülich to determine this substantial ARR. As tracer gas the environmentally friendly helium has been chosen. The helium is injected dynamically into the circular air flow of the system and the helium mole fraction is measured using a mass spectrometer. The dynamic concentration response of the system is used to determine the air return ratio. This dynamic method only requires one location of measurement. First measurements with this dynamic method were conducted at the solar tower Jülich. The ARR of STJ was measured with and without irradiation of the main receiver with high accuracy. Under low-wind conditions and without irradiation of the main receiver the air return ratio was measured to be ( 67.7 ± 0.5 ) % for an air mass flow of ( 9.96 ± 0.04 ) kg / s . A slightly higher air return ratio of ( 68.6 ± 0.7 ) % was measured under irradiation with an air mass flow of ( 9.94 ± 0.04 ) kg / s . The air return ratio was sensitive to the air mass flow, showing significantly lower rates when moving further away from the 10 kg / s design air mass flow to 5 kg / s .